Students' Perceptions of the Future of Devin AI: A Case Study at IPB University - Hardika, Bagus; Valencia, Cindy; Adzani, Rivanka Marsha; Barus, Irma Rasita Gloria; Fami, Amata (Insearch: Information System Research Journal, 2024)
Devin AI is an autonomous artificial intelligence assistant referred to as an "AI software developer" and claimed to be capable of building websites and applications, completing complex programming, and training its own AI models. Cognition Labs has released a trailer for Devin AI on YouTube. This research analyzes the responses of Software Engineering Technology students from the Vocational School of IPB University regarding the Devin AI trailer. Responses were collected via Google Forms from students of classes 59, covering familiarity, benefits, and concerns about using Devin AI. The responses varied, with both positive and negative feedback. Devin AI is considered capable of accelerating the software development process and allowing developers to focus on strategic and creative elements. 60% of respondents are not afraid that Devin AI will replace the position of Developer, seeing it as a companion or considering it a scam. Conversely, 40% are concerned that the Developer position will be replaced by Devin AI.